PERSEPSI GENERASI Z TERHADAP APLIKASI PEMESANAN TIKET BIOSKOP SECARA ONLINE - Indri Adhani; Yuli Susilawati; Ruswianti (Transpublika Publisher, 2022)
Enjoying a movie at a cinema may be an exciting experience for people who are enthusiastic about wide-screen motion pictures. This study seeks to examine Generation Z's perception of online applications for purchasing movie tickets. A total of ten respondents from Generation Z were surveyed regarding online applications for purchasing movie tickets. The researcher employs a qualitative descriptive method, while the model employed in this test is a technology-accepted model (TAM). The findings of this study indicate that the availability of an online cinema ticket booking application for generation z is seen as highly successful and advantageous, despite the presence of hurdles.